Asset Management, Cash Turnover, and Liquidity on Financial Performance With Capital Structure as Mediation - Sari, Triana; Nadhiroh, Umi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The fluctuating global economy has significantly affected the sustainability of the pharmaceutical industry, which plays an essential role in supporting public health. However, this sector still faces challenges in maintaining financial efficiency amid rapid growth. This study aims to examine the effect of asset management, cash turnover, and liquidity on financial performance, with capital structure as a mediating variable in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. The research employs a quantitative approach using panel data regression with secondary data obtained from annual financial reports. The sample consists of 10 pharmaceutical companies selected through purposive sampling. The study uses Return on Assets (ROA) to measure financial performance, Total Asset Turnover (TATO) for asset management, Cash Turnover (CTO) for cash flow efficiency, Current Ratio (CR) for liquidity, and Debt to Asset Ratio (DAR) for capital structure. The results show that asset management has a positive and significant effect on financial performance, while cash turnover and liquidity do not. Capital structure has a positive but insignificant effect on financial performance and does not mediate the relationship between asset management, cash turnover, and liquidity on financial performance. These findings indicate that improving asset utilization efficiency is crucial for enhancing profitability, while other operational aspects still require optimization to strengthen the financial structure of pharmaceutical companies.